Analisis Kualitas Pelayanan terhadap Tingkat Kepuasan Pelanggan pada Warung Nasi SPG - Indah Eva Saffanah (International Journal Administration, Business & Organization, 2023)
This study aims to determine the effect of service quality on the customer satisfaction level at SMEs Warung Nasi SPG in Bandung. Respondents come from customers who have made purchases at Warung Nasi SPG directly. This study uses a quantitative explanatory method, using validity test, reliability test, and simple linear regression tests. The sample in this study were 105 respondents. Data was collected by distributing questionnaires to respondents who fit the criteria. The result of this study indicates that there is a significant influence between service quality and the customer satisfaction level at Warung Nasi SPG.